A Dual Bioassay for Evaluation of Embryotoxicity and Acute Toxicity of Common Solvents and Surfactants in Artemia salina - Iulia Ioana Olaru; Octavian Tudorel Olaru; Dragos Paul Mihai; Cerasela Elena Gird; Anca Zanfirescu; Rica Boscencu; Emanuela-Alice Luta; Corina Andrei; George Mihai Nitulescu (Toxics, 2025)
This study evaluated the acute and developmental toxicity of selected hydrotropes, co-solvents, and surfactants commonly used in pharmaceutical and cosmetic formulations, using Artemia salina as a model organism. Two bioassays were employed: a lethality test and a hatching inhibition test. Compounds such as sodium lauryl sulfate (LC50 < 0.05%), sodium xylenesulfonate (LC50 = 0.79%), sodium p-toluensulfonate (LC50 = 0.21%), N,N-dimethylbenzamide (LC50 < 0.05%), and N,N-diethylnicotinamide (LC50 = 0.05%) exhibited high toxicity at 48 h, inducing significant mortality and strong inhibition of hatching. Glycerin, propylene glycol, and dimethyl sulfoxide showed low toxicity across all concentrations. Lethal concentration values confirmed the high toxicity of sodium xylenesulfonate and N,N-dimethylbenzamide, with moderate effects observed for other compounds. The hatching inhibition test proved more sensitive than the lethality test, enabling the detection of embryotoxicity and developmental delays. Although more laborious, it provided detailed information into how the tested substances influenced developmental stage progression. Hierarchical clustering analysis grouped the substances based on toxicity patterns and clearly discriminated highly toxic surfactants from low-toxicity solvents. The results demonstrated that combining both bioassays offers a more comprehensive evaluation of toxicity, with the hatching test being particularly useful for identifying early developmental effects not evident in lethality testing alone.